2018
DOI: 10.1055/s-0043-122070
|View full text |Cite
|
Sign up to set email alerts
|

Adenoma recurrence after endoscopic mucosal resection: propensity score analysis of old and new colonoscopes and Sydney recurrence tool implementation

Abstract: Background and study aims  Risk factors for colorectal adenoma recurrence after endoscopic mucosal resection (EMR) have been well documented. We assessed the efficacy of the newer 190 colonoscope versus the standard 180 colonoscope for complete resection of lateral spreading lesions. Patients and methods  A single-center, retrospective study of patients who underwent EMR with Olympus 180 or 190 colonoscopes from January 1, 2010 to September 30, 2016. We included patients with lesions ≥ 20 mm and surveillance c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…Our study highlights the risk of polyp recurrence at a surveillance endoscopy for the follow-up of an index polyp removed using CEMR and UEMR. Many studies have evaluated clinical and endoscopic predictors for recurrence [24,[26][27]. Our study showed a clear association between polyp size and degree of dysplasia and polyp recurrence, supporting what previous studies have consistently shown [19].…”
Section: Discussionsupporting
confidence: 89%
“…Our study highlights the risk of polyp recurrence at a surveillance endoscopy for the follow-up of an index polyp removed using CEMR and UEMR. Many studies have evaluated clinical and endoscopic predictors for recurrence [24,[26][27]. Our study showed a clear association between polyp size and degree of dysplasia and polyp recurrence, supporting what previous studies have consistently shown [19].…”
Section: Discussionsupporting
confidence: 89%
“…For example, we did not include epinephrine in the injection fluid. Recent studies have shown that intraprocedural hemorrhage is associated with an increased risk of residual lesion 12 , and anecdotally cold resection without epinephrine is clearly associated with a bloodier intraprocedural endoscopic field than when epinephrine is included in the injectate. Further, we did encounter some cases of persistent bleeding that was more than generalized oozing and included visible arterial hemorrhage, which we treated in some cases by clip application (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…However, the number of patients reported with cold piecemeal resection of large serrated lesions without submucosal injection is smaller. In general, cold resection techniques appear safer than resection techniques using electrocautery [5][6][7][8][9][10][11][12] , with a much reduced or negligible risk of delayed postpolypectomy hemorrhage, and negligible risk of postpolypectomy syndrome and perforation.…”
Section: Introductionmentioning
confidence: 99%
“…However, we could not demonstrate an association between HGD and adenoma recurrence at 6 months. Previous research also failed to demonstrate this association [6, 9]. Arguably, a higher number of patients would be necessary to evaluate the association of HGD with 6-month adenoma recurrence, as was performed by Tate et al [8].…”
Section: Discussion/conclusionmentioning
confidence: 98%
“…Some endoscopic features and procedural variables have been linked to greater risk of recurrent adenoma. Several studies demonstrated the association between large lesion size and adenoma recurrence [ 6 , 7 , 8 , 9 ]. Additionally, localization in the right colon, namely involving the ileocecal valve or the appendix orifice, and intraprocedural bleeding (IPB) were also associated with recurrent lesions [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%